Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1002/ijc.2910550620
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic blood transfusion reduces murine pulmonary natural killer (NK) activity and enhances lung metastasis of a syngeneic tumour

Abstract: A model was established whereby C57BL/6 (B6) blood injected i.v. into C3H mice 7 days prior to i.v. injection of syngeneic UV-2237 tumour cells significantly increased the number of pulmonary metastases counted 21 days later as compared with levels observed in mice treated with saline, C3H or NZW blood or SRBC. This regimen of B6 allogeneic blood transfusion of C3H mice also significantly depressed splenic and pulmonary NK activity as assayed by lysis of 51Cr YAC-I in vitro and by clearance of 111In YAC-I in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…An adverse effect of blood transfusion on natural killer and T-lymphocyte function might also be associated with changes in cancer behavior [32,33] . Using an in vivo experimental system, Clarke et al [34] concluded that suppression of natural killer cell activity by allogeneic blood transfusion augments metastasis. With the aim of minimizing transfusion-associated immunomodulatory effects that induce increased morbidity and poor prognosis in cancer patients, transfusion of leukocyte-depleted packed red blood cells has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…An adverse effect of blood transfusion on natural killer and T-lymphocyte function might also be associated with changes in cancer behavior [32,33] . Using an in vivo experimental system, Clarke et al [34] concluded that suppression of natural killer cell activity by allogeneic blood transfusion augments metastasis. With the aim of minimizing transfusion-associated immunomodulatory effects that induce increased morbidity and poor prognosis in cancer patients, transfusion of leukocyte-depleted packed red blood cells has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific cytotoxic lymphocytes as well as macrophages play important roles in the prevention of lymph node and distant metastases [14]. The inhibition of metastasis by these cells must be thoroughly investigated in order to explore the mechanism of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that tumor cell metastasis is under the regulation of the cellular immunity of the host [5, 14, 15]. Nonspecific cytotoxic lymphocytes as well as macrophages play important roles in the prevention of lymph node and distant metastases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most data emerged from animal studies, where the level of NK activity was correlated with tumor progression [38,39,43,44]. However, a study in humans also showed that pre operative NK activity correlated with an increased risk of tumor recurrence [32], It has recently been shown that in colorectal cancer patients, disseminated tumor cells found at curative surgery of even early tumor stages demonstrated a prognostic impact [45].…”
Section: Blood Transfusion and Nk And Lak Activitiesmentioning
confidence: 99%
“…The effect on NK activity has been investigated, both ex perimentally [38,39] and clinically [29,30,34,40,41]. Most authors report a transfusion-associated NK suppres sion which, however, was not seen in two studies [31,42].…”
Section: Modulation By Autologous Blood Transfusionmentioning
confidence: 99%